Dosage-sensitive function of Retinoblastoma related and convergent epigenetic control are required during the Arabidopsis life cycle - Johnston, Amal Joseph; Kirioukhova, Olga; Rutten, Twan; Moore, James M.; Grossniklaus, Ueli; Gruissem, Wilhelm (PLoS Genetics, 2010)
Author Summary Understanding the convergent developmental mechanisms of core cell cycle genes is highly instructive in biology. When these genes are essential in development, lethality precludes mutation analysis throughout the life cycle of an organism. We subjected a homozygous lethal mutation in RETINOBLASTOMA RELATED (RBR) of Arabidopsis for tetraploid genetic analysis to study the function of RBR during the plant life cycle. In diploids, while RBR-deficient female gametophytes with features of aberrant cell fate and differentiation were analogous to what was previously reported for male gametophytes, we provide evidence that RBR controls gametic genome duplication, thus genome integrity in the gametophyte-derived progeny. Quantitative reduction of RBR in tetraploids led to identification of rbr heterozygous plants that displayed novel RBR dosage-dependent phenotypes in differentiation and development of the sporophyte albeit the absence of cell cycle defects. These phenotypes coincided with deregulation of conserved epigenetic factors such as Polycomb Repressive Complex 2 (PRC2) genes and METHYLTRANSFERASE 1 (MET1) in the sporophyte, as shown for the gametophytes as well. However, unlike the repression by the PRC2 in gametophytes, RBR is activated by the sporophytic PRC2 subunits, suggesting that distinct modules of the conserved RBR-PRC2-MET1 loop control gametophyte and sporophyte generations in plants.